La notion de patrimoine immatériel comme outil de contournement de l’État : enjeux et ambiguïtés de la fabrique patrimoniale du gwoka en Guadeloupe - Florabelle Spielmann; Dominique Cyrille (Transposition)
Paris, November 26, 2014: Guadeloupe gwoka is inscribed on the Representative List (RL) of the UNESCO Convention for safeguarding Intangible Cultural Heritage (ICH). Traditional gwoka is a dance performed to the sound of ka drums and call-and-response singing. It takes place at night during festive events called léwoz. In this article, we want to contribute to the discussion of the ways in which communities make use of the notion of Cultural Heritage. It is based on ethnographic data gathered between 2006 and 2015 through participant observation. It discusses the impact that gwoka's inscription on the RL of the ICH had on the gwoka community. It wants to shed light on some of the political stakes that inscribing a cultural expression on the RL of the ICH Convention entails. This article opens on a presentation of a brochure titled Rapport culturel, which was published in 1970 by the General Association of Guadeloupean Students (AGEG). The Rapport culturel is a founding document that formulates a “specific claim that gwoka is a core component of the cultural personality of the Guadeloupean people”. This document compelled Guadeloupeans of the 1970s and 80s to undertake a variety of actions aiming at making Gwoka a defining element of their cultural heritage. Second, we examine the ways in which the notion of ICH began to circulate in Guadeloupe, a place where heritagisation processes are well underway. Contrary to what has been observed elsewhere, in Guadeloupe the tradition bearers were the ones who initiated the spread of ICH, not the State. Finally, we focus on the vibrant debate the inscription process has sparked, thus transforming gwoka into a political arena where notions of power and identity are contested, re-discussed and re-imagined.